Mathematical Modeling and Sensitivity Analysis on Cadmium Transport in Kaolinite under Direct Current Electric Field - Milad Rezaee; Mostafa Nasrollahi Gisel; Saman Saffari (Salehan Institute of Higher Education, 2017)
Soil pollution is a challenging concern for environmentalists. Different remediation methods have been proposed to remediate polluted soils. Most of the existing methods cannot purify low permeable soils. Electrokinetic remediation (EKR) is an effective method which can remediate fine-grained soils. Understanding the physicochemical phenomena of the EKR is necessary to achieve efficient experimental framework. Therefore, the present study aims to introduce a theoretical and mathematical model for the EKR process. In the present model, different transport phenomena including ion migration, electroosmotic flow, and diffusion were considered. In addition, Chemical reactions such as adsorption/desorption, precipitation/dissolution, water autoionization reaction, and electrolysis reaction were considered. For modeling purpose, a set of partial differential and algebraic equations were used to model the remediation process. The implicit finite difference numerical model showed a good capability of simulating the EKR process. The sensitivity analysis on the retardation and tortuosity factors represented that the retardation factor had a considerable effect on the pH and cadmium concentration profiles. Although tortuosity factor did not have a significant impact on the pH profile, it had a non-negligible effect on the cadmium concentration profile.